2021
DOI: 10.1039/d0tc04307a
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal of two-dimensional mixed-halide copper-based perovskites with reversible thermochromism

Abstract: Facile synthesis of single crystal of two-dimensional mixed-halide copper-based perovskites with tunable band gaps and their capability of exfoliation and reversible thermochromism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 41 publications
5
56
0
Order By: Relevance
“…[15][16][17][18] Attributed to the fact that the cesium cation Cs + (167 pm) has a smaller ionic radius than the methyl ammonium cation (MA) + (217 pm) cations, the perovskite crystal lattice contraction is expected. [19] While mixed halides play an important role in tuning the properties and stability of hybrid perovskites beyond pure halide perovskites, [20][21][22] understanding the effect of inorganic/organic mixed cations on the perovskite crystal lattice is critical not only for reducing potential degradation pathways but also for obtaining tunable perovskites properties. [23] The bandgaps of mixed-cation lead-based perovskite Cs x (MA) 1À x PbBr 3 which revealed a bimodal distribution, with bandgaps close to those of pure MAPbBr 3 for x � 0.13 and pure CsPbBr 3 for x > 0.13 according to Liu and his colleagues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Attributed to the fact that the cesium cation Cs + (167 pm) has a smaller ionic radius than the methyl ammonium cation (MA) + (217 pm) cations, the perovskite crystal lattice contraction is expected. [19] While mixed halides play an important role in tuning the properties and stability of hybrid perovskites beyond pure halide perovskites, [20][21][22] understanding the effect of inorganic/organic mixed cations on the perovskite crystal lattice is critical not only for reducing potential degradation pathways but also for obtaining tunable perovskites properties. [23] The bandgaps of mixed-cation lead-based perovskite Cs x (MA) 1À x PbBr 3 which revealed a bimodal distribution, with bandgaps close to those of pure MAPbBr 3 for x � 0.13 and pure CsPbBr 3 for x > 0.13 according to Liu and his colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to literatures, mixed-halides of all MA Cuperovskites, that is, (CH 3 NH 3 ) 2 Cu(Cl/Br) 4 , are easily exfoliated into two-dimensional (2D) perovskites. [20,21] On the other hand, mixed-halides of all Cs Cu-perovskites, that is, Cs 2 Cu(Cl/Br) 4 with different crystal structures depending on the halogen content, cannot be exfoliated into separated flakes. [42][43][44][45] Herein, easily exfoliated 2D mixed-halides of all Cs perovskite are prepared through using excess concentration of cesium bromide (CsBr).…”
Section: Introductionmentioning
confidence: 99%
“…[18] Hayashi et al reported TCM in Cu-based perovskite (CH 3 NH 3 ) 2 CuCl x Br 4 −x thin films obtained by the exfoliation of its single crystals (SC). [19] Gao et al demonstrated TCM in double perovskite Cs 2 AgBiBr 6 . [20] But, these materials showed high temperature TCM that prompted us to look for materials that are stable and can show the TCM property at lower temperature.…”
Section: Reversible Thermochromism In All-inorganic Lead-free Cs 3 Sb 2 I 9 Perovskite Single Crystalsmentioning
confidence: 99%
“…reported TCM in Cu‐based perovskite (CH 3 NH 3 ) 2 CuCl x Br 4 − x thin films obtained by the exfoliation of its single crystals (SC). [ 19 ] Gao et al. demonstrated TCM in double perovskite Cs 2 AgBiBr 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Using, Cu, as a cheap, earth-abundant and non-toxic element, to develop Cu-based 2D perovskite materials was expected to be an ideal substitute due to the stable structures and the antioxidant ability. [16] Unfortunately, the solar cell fabricated with a layered (CH 3 NH 3 ) 2 CuCl 4À x Br x perovskite as the light absorption layer only exhibited a photoelectric conversion efficiency (PCE) of 0.017 %, [17] which was severely limited by its wide band gap and poor carrier transport performance. Photovoltaic devices using perovskite-like (CH 3 CH 2 CH 2 CH 2 NH 3 ) 2 CuBr 4 and (FÀ C 8 H 8 NH 3 ) 2 CuBr 4 were reported to exhibit good stability in air with 50 % humidity for one day, but the conversion efficiency is still quite low at 0.51-0.63 %.…”
Section: Introductionmentioning
confidence: 99%